PROTOTYPE ALAT UJI KEBISINGAN DAN EMISI GAS PADA KNALPOT KENDARAAN BERMOTOR MENGGUNAKAN ARDUINO UNO - Nuraida_Latif Ida (LPPM Universitas Al Asyariah Mandar, 2022)
Transportation from every era has always been a special concern for the government in Indonesia. This is inseparable from the increasing number of motorcycle users, so that the increase in the number of vehicles clearly has a negative impact on health, especially from smoke pollution which contains carbon monoxide (CO) compounds produced or from the noise. This study aims to determine the level of noise and gas emissions in vehicle exhaust. The tool used to measure gas emissions is MQ-2 while noise is measured by a sound sensor which is then processed on the Arduino and then displayed on the LCD. This type of research is exploratory observation and data analysis is described descriptively. The results of the study are a tool that is able to detect gas emissions and noise in the motorcycle exhaust with a sound sensor response of 2-3 seconds while the Mq2 sensor with a response time of 5-6 seconds takes longer.